ASSOCIATION BETWEEN THE AGE OF PREGNANT WOMEN AND PARITY WITH THE INCIDENCE OF PLACENTA PREVIA : SYSTEMATIC REVIEW - Tegar Perbawa, Prayudha; Juliana, Mutia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Placenta previa is associated with an increased risk of premature birth, fetal death during intrauterine development, and asphyxia in neonates. Vaginal bleeding that is not unpleasant is one of the telltale signs of placenta previa. It is estimated that 5.2% of pregnancies would be affected by the common obstetric condition known as placenta previa. Sometimes there are no symptoms associated with placenta previa. During the second half of pregnancy, the primary symptom is vaginal bleeding that is brilliant red and completely painless. Moreover, this syndrome can cause excessive bleeding prior to or throughout the labor process. The uterus should have some scars on it as a result of a surgery or procedure that was performed in the past. a previous pregnancy in which you experienced placenta previa is considered to be a risk factor. Having a previous cesarean section (CS), having an abortion, being older than 35 years old, having more than one child, and using assisted reproductive technologies (ART) such in vitro fertilization are all variables that can increase the likelihood of developing placenta previa (IVF). It appears that the risk of placenta previa increases with both the mother's age and the number of previous pregnancies. Despite the fact that research has shown that the association is not consistent at all.